PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Teguh Gunawan Setyabudi; Susanti; Dini Widyawati; Ulfah Setia Iswara (LPPM STIE YKPN Yogyakarta, 2025)
This study aims to empirically test the effect of profitability and leverage on company value. This study is a quantitative study. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2020-2023. The sample companies were 55 companies. Profitability variables are measured using return on equity (ROE), leverage variables are measured using debt to asset ratio (DAR), and company value variables are measured using price to book value (PBV). Data analysis was carried out using multiple linear regression analysis. The results of the study show that profitability has no effect on company value, while leverage has a negative effect on company value. Companies with high debt will cause the company value to decrease.